1.5 Minute-synthesis of continuous graphene films by chemical vapor deposition on Cu foils rolled in three dimensions. (29th June 2019) - Nagai, Yukuya; Sugime, Hisashi; Noda, Suguru
Graphical abstract: Highlights: High-productivity CVD process/condition is reported for continuous graphene films. Graphene is synthesized on a large Cu foil rolled in 3D and set in a small reactor. Continuous graphene film is obtained uniformly at 975 °C in 1.5 min using C2 H4 . The graphene is of high quality (95.7% transmittance, 0.3 kΩ sq −1 sheet resistance). Highest productivity per reactor volume and process time (heating, annealing, CVD). Abstract: We report a high-productivity chemical vapor deposition (CVD) process of graphene by extending the reaction field to three dimensions (3D) and shortening the CVD time to a few minutes. A large Cu foil (5 × 30 cm 2 ) is rolled up and set in a small reactor (3.4 cm in diameter), and a continuous graphene film is obtained uniformly in a short time (1.5 min) by using C2 H4 as a more reactive carbon source than the popular CH4 . The graphene transferred onto a quartz glass showed optical transmittances of 94.8–96.7% (550 nm) with sheet resistances of 0.78–1.68 kΩ sq −1 (without doping) and 0.3 kΩ sq −1 (with doping by HNO3 vapor). Compared with the previous reports for fast and/or large-scale CVD, our method realized similarly high productivity of 100 cm 2  min −1 based on the CVD time despite of the small reactor, and higher productivity of 0.03 cm 2 -graphene per cm 3 -reactor per minute based on the reactor volume and total time for high temperature processing (15 min for heating, 1 min for annealing, and 1.5 min for CVD). The knowledge obtained here on the CVD conditions and packing ratio of Cu foils (0.55 cm 2 per cm 3 -reactor) is reusable for designing large-scale graphene production processes.